CD147 in Cardiovascular Disease and Thrombosis - Pennings, Gabrielle J.; Kritharides, Leonard (Seminars in Thrombosis and Hemostasis, 2014)
Thrombotic and inflammatory pathways play a key role in coronary artery disease (CAD) development. Extracellular matrix metalloproteinase (aka CD147) is a member of the immunoglobulin superfamily that is expressed on many cell types including hematopoietic, endothelial cells, leukocytes, keratinocytes, platelets, and others. The binding partners of CD147 are numerous and diverse, and give some indication to the various roles that CD147 can play; these include homophilic interactions, integrins, cyclophilins, glycoprotein VI (GPVI), caveolin 1, and monocarboxylate transporters. Recent evidence suggests a role for CD147 in both thrombosis and inflammation, as well as involvement in CAD and cancer. In this review, we summarize the role of CD147 and its binding partners in platelets, thrombosis, and arterial disease and assess mechanistic aspects of CD147 biology.
Keywords: CD147; EMMPRIN; CAD; thrombosis; cyclophilin